The animal question: the Anthropocene’s hidden foundational debate - Abel A. Alves (História, Ciências, Saúde - Manguinhos, 2021)
As globalization accelerated after 1492, often in the service of European imperial expansion, human destruction of the habitat in which animals could express their natural behaviors also increased. Within this context, the question arises: just how much are we like other animals, and if they are like us, how much do we owe them? From the 1500s to the 1800s, travelers, imperialists, the colonized, and intellectuals tried to answer this question and produced three positions: animals as mere exploitable devices; confusion about animals’ status and what we owe them, and concern about the suffering of nonhuman animals, their freedom to express their behaviors, and their very existence.